Lithium iron phosphate material, method for preparing the same, and secondary battery

CN123002803APending Publication Date: 2026-10-30WANHUA CHEM GRP BATTERY TECH CO LTD +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611166518.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而传统的磷酸铁锂材料在高压实密度下的过充性能较差,亟需改善

Benefits of technology

[0044]上述的磷酸铁锂材料的制备方法,采用有机锰源和含巯基有机物作为掺杂剂,烧结过程中有机锰源中的锰元素与含巯基有机物中的巯基形成Mn-S配位键,利用有机锰源和含巯基有机物形成的分子对,在待处理磷酸铁锂物料表面构建Mn-S键合修复位点,定向钝化铁空位并抑制电解液侵蚀,阻止铁离子溶出,从而提升材料的过充性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a lithium iron phosphate material, a preparation method thereof and a secondary battery. The lithium iron phosphate material comprises lithium iron phosphate particles and a carbon coating layer coated on at least part of the surface of the lithium iron phosphate particles. The lithium iron phosphate particles are doped with manganese elements and sulfur elements. At least part of the manganese elements and at least part of the sulfur elements form Mn-S coordination bonds. The Mn-S coordination bonds in the material act as Mn-S bonding repair sites, can direct passivation of iron vacancies and inhibit electrolyte corrosion, prevent iron ion dissolution, and thus improve the overcharge performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary battery cathode materials technology, and in particular to lithium iron phosphate materials, their preparation methods, and secondary batteries. Background Technology

[0002] With the continuous development of battery applications, battery technology has advanced rapidly. Lithium iron phosphate materials, due to their advantages such as high safety, long cycle life, and controllable cost, are widely used in new energy vehicles, energy storage systems, and consumer electronics.

[0003] With the widespread application of lithium-ion batteries in new energy vehicles, energy storage systems, and other fields, people have increasingly higher requirements for battery safety performance, which in turn places higher demands on battery overcharge performance. However, traditional lithium iron phosphate materials have poor overcharge performance under high density, which urgently needs improvement. Summary of the Invention

[0004] Based on this, this application provides a lithium iron phosphate material with low iron dissolution under high pressure density and excellent overcharge performance, as well as its preparation method and secondary battery.

[0005] The first aspect of this application provides a lithium iron phosphate material, comprising lithium iron phosphate particles and a carbon coating layer covering at least a portion of the surface of the lithium iron phosphate particles, wherein the lithium iron phosphate particles are doped with manganese and sulfur, and at least a portion of the manganese and at least a portion of the sulfur form Mn-S coordination bonds.

[0006] In some embodiments, the concentration distribution of manganese and sulfur elements increases radially from the center of the lithium iron phosphate particle to its outer surface.

[0007] In some embodiments, the manganese element in the Mn-S coordination bond is connected to its neighboring iron element through a lattice oxygen bridge.

[0008] In some embodiments, the lithium iron phosphate material is also doped with nitrogen.

[0009] In some embodiments, the mass percentage of manganese in the lithium iron phosphate material is 0.26%-0.64%.

[0010] In some embodiments, the Dv50 of the lithium iron phosphate material is 1100nm-1500nm.

[0011] In some embodiments, the Dv50 of the lithium iron phosphate material is 1200nm-1400nm.

[0012] In some embodiments, the specific surface area of ​​the lithium iron phosphate material is 9m². 2 / g-14m 2 / g.

[0013] In some embodiments, the specific surface area of ​​the lithium iron phosphate material is 10 m². 2 / g-12m 2 / g.

[0014] In some embodiments, the carbon coating layer accounts for 1.05%-1.35% of the mass of the lithium iron phosphate material.

[0015] In some embodiments, the lithium iron phosphate particles further contain an element M, which includes one or more of Ti, V, Nb, Mg, W, and Y.

[0016] In some embodiments, the compaction density of the lithium iron phosphate material is 2.55 g / cm³. 3 -2.6g / cm 3 .

[0017] A second aspect of this application provides a method for preparing lithium iron phosphate material, comprising the following steps:

[0018] The lithium iron phosphate material is prepared by first sintering a first system comprising the lithium iron phosphate material to be treated, an organomanganese source, a mercapto-containing organic compound, and a first carbon source under a first inert atmosphere.

[0019] In some embodiments, the organomanganese source contains a six-membered conjugated chelate ring.

[0020] In some embodiments, the organic manganese source includes one or more of manganese acetylacetone, manganese benzoylacetone, manganese hexafluoroacetylacetone, and manganese dibenzoylmethane.

[0021] In some embodiments, the thiol-containing organic compound includes one or more of thiol-containing amino acids, thiol-containing carboxylic acids, and thiol-containing alcohols.

[0022] In some embodiments, the thiol-containing amino acid includes one or more of L-cysteine, D-cysteine, L-homocysteine, and L-cysteine.

[0023] In some embodiments, the percentage of manganese in the organic manganese source relative to the mass of the first system is 0.21%-0.72%.

[0024] In some embodiments, the percentage of manganese in the organic manganese source relative to the mass of the first system is 0.26%-0.64%.

[0025] In some embodiments, the thiol-containing organic compound accounts for 0.5%-1.5% of the mass of the first system.

[0026] In some embodiments, the thiol-containing organic compound accounts for 0.8%-1.2% of the mass of the first system.

[0027] In some embodiments, the temperature of the first sintering treatment is 650°C-790°C, and the time is 5h-12h.

[0028] In some embodiments, the mass percentage of the first carbon source in the first system is 0.5%-5%.

[0029] In some embodiments, the first carbon source includes at least one of glucose, sucrose, fructose, starch, polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol.

[0030] In some embodiments, the method for preparing the lithium iron phosphate material to be treated includes: providing a second system comprising an iron source, a phosphorus source, a lithium source, and a second carbon source; drying the second system to prepare a material to be sintered; and performing a second sintering treatment on the material to be sintered under a second inert atmosphere to prepare the lithium iron phosphate material to be treated.

[0031] In some embodiments, the molar ratio of lithium in the lithium source to iron in the iron source is (1.02-1.1):1.

[0032] In some embodiments, the molar ratio of iron in the iron source to phosphorus in the phosphorus source is (0.96-0.985):1.

[0033] In some embodiments, the second carbon source accounts for 0.5%-5% of the mass of the second system.

[0034] In some embodiments, the temperature of the second sintering treatment is 500℃-800℃, and the time is 3h-10h.

[0035] In some embodiments, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium phosphate, lithium dihydrogen phosphate, and lithium acetate.

[0036] In some embodiments, the iron source includes one or more of ferric oxide, iron tetroxide, ferric hydroxide, ferric nitrate, and ferric phosphate.

[0037] In some embodiments, the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium phosphate, and lithium dihydrogen phosphate.

[0038] In some embodiments, the second carbon source includes one or more of glucose, sucrose, fructose, starch, polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol.

[0039] In some embodiments, the second system further includes additives.

[0040] In some embodiments, the additive comprises a compound containing an element M, wherein the element M includes one or more of Ti, V, Nb, Mg, W, and Y.

[0041] In some embodiments, the additive accounts for 0.1%-2% of the mass of the second system.

[0042] The third aspect of this application provides a secondary battery, including at least one of the lithium iron phosphate material of the first aspect of this application and the lithium iron phosphate material prepared by the preparation method of the second aspect of this application.

[0043] In the aforementioned lithium iron phosphate materials, the Mn-S coordination bonds serve as Mn-S bond repair sites, and their Mn... 2+ / Mn 3+ The redox couple has approximately 4.1 V (vs. Li). + The redox potential of MnFe(II) can preferentially provide electrons over electrolyte decomposition at high voltages, forming an electron trap effect, thereby stabilizing the interface and inhibiting electrolyte erosion. Simultaneously, the introduction of sulfur (S) increases the migration activation energy of neighboring iron ions from 1.2 eV to 1.8 eV, constructing an effective ion diffusion barrier and significantly preventing iron ion dissolution. Furthermore, the Mn-S coordination bond can reversibly absorb overcharge energy at voltages above 4.2 V through dynamic bonding changes. Through the synergistic effect of these mechanisms, the lithium iron phosphate material of this invention exhibits significantly improved overcharge performance.

[0044] The above-mentioned method for preparing lithium iron phosphate materials uses an organic manganese source and a mercapto-containing organic compound as dopants. During the sintering process, the manganese element in the organic manganese source forms Mn-S coordination bonds with the mercapto groups in the mercapto-containing organic compound. The molecular pairs formed by the organic manganese source and the mercapto-containing organic compound are used to construct Mn-S bond repair sites on the surface of the lithium iron phosphate material to be treated, thereby directionally passivating iron vacancies and inhibiting electrolyte erosion, preventing iron ion dissolution, and thus improving the overcharge performance of the material. Detailed Implementation

[0045] To facilitate understanding of this application, a more complete description of the application will be provided below with reference to relevant embodiments. Preferred embodiments of the application are given below. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of this application.

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0047] As used herein, the terms "and / or," "or / and," and "and / or" encompass any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected using at least two conjunctions selected from "and / or," "or / and," and "and / or," it should be understood that, in this application, the technical solution undoubtedly includes solutions connected by "logical AND," and also undoubtedly includes solutions connected by "logical OR."

[0048] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0049] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0050] This document only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.

[0051] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows temperature fluctuations within the precision range controlled by the instrument, such as ±5°C, ±4°C, ±3°C, ±2°C, or ±1°C.

[0052] In this document, the term "suitable" as used in phrases such as "suitable combination," "suitable method," and "any suitable method" refers to the ability to implement the technical solution of this application, solve the technical problem of this application, and achieve the expected technical effect of this application.

[0053] In this application, terms such as "further," "even further," and "particularly" are used to describe purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.

[0054] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.

[0055] In the description of the application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0056] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.

[0057] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, but sequentially is preferred.

[0058] Traditional lithium iron phosphate (LFP) materials exhibit poor overcharge performance under high density conditions. The amount of iron dissolved from LFP materials is closely related to battery overcharge performance; the higher the iron dissolved amount, the worse the battery's overcharge performance. Therefore, limiting iron dissolution from LFP materials is key to improving battery overcharge performance.

[0059] Based on the above problems, this application mixes the lithium iron phosphate material to be processed with an organic manganese source and a mercapto-containing organic compound and then performs sintering treatment. During the sintering treatment, the manganese element in the organic manganese source forms Mn-S coordination bonds with the mercapto groups in the mercapto-containing organic compound. The resulting lithium iron phosphate material has low iron dissolution under high pressure density and excellent overcharge performance.

[0060] The first aspect of this application provides a lithium iron phosphate material, including lithium iron phosphate particles and a carbon coating layer covering at least a portion of the surface of the lithium iron phosphate particles, wherein the lithium iron phosphate particles are doped with manganese and sulfur elements, and at least a portion of the manganese elements and at least a portion of the sulfur elements form Mn-S coordination bonds.

[0061] Understandably, in the lithium iron phosphate material of this application, the Mn-S coordination bond serves as the Mn-S bond repair site, and its Mn 2+ / Mn3+ The redox couple has approximately 4.1 V (vs. Li). + The redox potential of MnO2 (Li) allows it to preferentially provide electrons over electrolyte decomposition at high voltages, forming an electron trapping effect that directionally passivates iron vacancies and inhibits electrolyte corrosion. The introduction of sulfur significantly increases the migration barrier of neighboring iron ions from 1.2 eV to 1.8 eV, forming an ion diffusion barrier and preventing iron ion dissolution. Furthermore, the Mn-S coordination bond can absorb overcharge energy through dynamic bonding changes above 4.2 V. Through the synergistic effect of these factors, the overcharge performance of the material is significantly improved.

[0062] As an example, the Mn-S coordination bonds in lithium iron phosphate particles mentioned in the context can be tested using X-ray photoelectron spectroscopy (XPS), X-ray absorption fine structure spectroscopy (XAS), and EELS surface analysis based on scanning transmission electron microscopy (STEM); specifically as follows: XPS spectra are obtained by performing XPS tests on lithium iron phosphate particles, and in-depth analysis of XPS (combined with Ar) is performed. + (Sputtering) It can be observed that even after sputtering removes the surface layer, the signals of Mn and S persist, indicating that the coordination is not limited to the particle surface. Secondly, synchrotron XAS analysis provides direct evidence of the bulk structure, confirming that the Mn-S coordination is ubiquitous inside the particles. Finally, based on the EELS surface distribution, it is further revealed that the signals of Mn and S exhibit obvious co-localization characteristics in the iron-vacancy enrichment region, thus strongly supporting the spatial correlation between Mn-S coordination bonds and iron vacancies.

[0063] In some embodiments, the concentration distribution of manganese and sulfur elements increases radially from the center of the lithium iron phosphate particle to its outer surface. This allows the surface-enriched manganese and sulfur elements to preferentially form a Mn-S passivation layer, trapping dissolved iron ions at the interface, effectively suppressing electrolyte corrosion and reducing iron dissolution, thereby improving the overcharge performance of the material.

[0064] In some implementations, after Mn atoms occupy iron vacancies, they connect with neighboring iron atoms through lattice oxygen bridges (Mn-O-Fe), while Mn forms direct Mn-S bonds with S in the surface modifier. This blocks the formation pathway of Fe-S coordination bonds, further suppressing iron dissolution and improving the battery's overcharge performance.

[0065] As one possible implementation, the manganese element in the Mn-S coordination bond is connected to its neighboring iron element through a lattice oxygen bridge. This helps to block the formation path of the Fe-S coordination bond, further suppressing iron dissolution and improving the battery's overcharge performance.

[0066] As an example, to confirm the structural characteristics of the Mn-S coordination bonds in lithium iron phosphate particles and their spatial relationship with iron vacancies, a combination of XPS depth profiling, synchrotron XAS, EXAFS, and STEM-EELS was used for characterization, specifically: Ar + Sputtering depth profiling (XPS) revealed that Mn and S signals continued to coexist after the surface layer was removed, and chemical state analysis confirmed Mn-S bonding, indicating that the coordination has a certain depth distribution rather than being limited to the surface layer. Bulk-sensitive synchrotron XAS (fluorescence mode) showed Mn-S coordination signals in both XANES and EXAFS, confirming that Mn-S coordination is ubiquitous inside the particles. EXAFS fitting of the Mn-K edge yielded Mn-O bond lengths of 1.92 Å and Mn-S bond lengths of 2.36 Å. Further multiscattering path analysis revealed that the Mn-O-Fe bond angle was 164.3 ± 2°, exhibiting a near-linear oxygen bridge structure, directly confirming that Mn atoms in the Mn-S coordination bond are connected to neighboring Fe atoms through lattice oxygen bridges. High-resolution STEM-EELS surface distribution revealed that Mn and S signals co-located and enriched in the iron vacancy region, providing spatial correlation evidence for the targeted stabilization of iron vacancies by the Mn-S coordination bond.

[0067] In some embodiments, the lithium iron phosphate material is also doped with nitrogen.

[0068] In one possible implementation, the mass percentage of manganese in the lithium iron phosphate material is 0.26%-0.64%. For example, it can be, but is not limited to, 0.26%, 0.28%, 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, 0.4%, 0.42%, 0.44%, 0.46%, 0.48%, 0.5%, 0.52%, 0.54%, 0.56%, 0.58%, 0.6%, 0.62%, 0.64%, or any range between any two of the above values. Thus, manganese ions can suppress oxygen vacancy migration through lattice pinning effect, while simultaneously delaying carrier recombination.

[0069] It should be noted that the mass percentage of manganese in lithium iron phosphate materials mentioned in the context refers to the total mass percentage of all manganese elements contained in the lithium iron phosphate materials.

[0070] In some embodiments, the Dv50 of the lithium iron phosphate material is 1100nm-1500nm; for example, it can be, but is not limited to, 1100nm, 1150nm, 1200nm, 1250nm, 1300nm, 1350nm, 1400nm, 1450nm, 1500nm, or any range between two of the above particle sizes. This is beneficial for balancing the compaction density and electrical properties of the lithium iron phosphate material.

[0071] In some alternative implementations, the Dv50 of the lithium iron phosphate material is 1200nm-1400nm.

[0072] As an example, the Dv50 mentioned in the context can be tested using a laser particle size analyzer.

[0073] In some embodiments, the specific surface area of ​​the lithium iron phosphate material is 9m². 2 / g-14m 2 / g; for example, it can be, but is not limited to, 9m. 2 / g, 10m 2 / g、11m 2 / g、12m 2 / g、13m 2 / g、14m 2 / g or the range between any two of the above specific surface areas, etc.

[0074] In some optional embodiments, the specific surface area of ​​the lithium iron phosphate material is 10 m². 2 / g-12m 2 / g.

[0075] As an example, the specific surface area mentioned in the context can be tested using the following method: The powder sample to be tested is placed in a U-shaped sample tube, and a mixed gas containing a certain proportion of adsorbate molecules (N2) is passed through the sample. The amount of adsorbate molecules (N2) adsorbed by the sample is determined based on the change in gas concentration before and after adsorption. Specific procedures can be found in standard GB / T13390-2008.

[0076] In some embodiments, the carbon coating layer accounts for 1.05%-1.35% of the mass of the lithium iron phosphate material; for example, it can be, but is not limited to, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, or any range between any two of the above mass percentages.

[0077] As an example, the mass percentage of the carbon coating in lithium iron phosphate materials mentioned in the context can be determined using the following method:

[0078] The lithium iron phosphate material to be tested is heated and burned in an oxygen stream in a high-frequency induction furnace. The generated carbon dioxide and sulfur dioxide are carried by the oxygen to the measuring chamber of an infrared analyzer. Since carbon dioxide and sulfur dioxide absorb infrared energy of specific wavelengths, and their absorption energy is proportional to their concentration, the carbon and sulfur content of the sample can be measured based on the change in energy received by the detector. For specific operation, please refer to the standard: GB / T 20123-2006.

[0079] In some embodiments, the lithium iron phosphate particles also contain an element M, which includes one or more of Ti, V, Nb, Mg, W, and Y.

[0080] As one possible implementation, the compaction density of the lithium iron phosphate material is 2.55 g / cm³. 3 -2.60 g / cm 3 For example, it can be, but is not limited to, 2.55 g / cm³. 3 2.56 g / cm 3 2.57g / cm 3 2.58g / cm 3 2.59g / cm 3 2.6g / cm 3 Or the range between any two of the above compaction densities, etc.

[0081] The second aspect of this application provides a method for preparing lithium iron phosphate material, which can be used to prepare the aforementioned lithium iron phosphate material. The method includes the following steps: under a first inert atmosphere, a first system comprising lithium iron phosphate material to be treated, an organomanganese source, a mercapto-containing organic compound, and a first carbon source is subjected to a first sintering treatment to prepare the lithium iron phosphate material.

[0082] Understandably, the preparation method of lithium iron phosphate material in this application uses an organic manganese source and a mercapto-containing organic compound as dopants. During sintering, the manganese element in the organic manganese source forms Mn-S coordination bonds with the mercapto groups in the mercapto-containing organic compound. Utilizing the synergistic effect of the two on the surface of the lithium iron phosphate material to be treated, Mn-S bond repair sites are constructed, which directionally passivate iron vacancies and inhibit electrolyte erosion, preventing iron ion dissolution, thereby improving the overcharge performance of the material.

[0083] It should be noted that the lithium iron phosphate material prepared by this method has similar technical solutions and beneficial effects to the lithium iron phosphate material mentioned above, and will not be elaborated further here.

[0084] In some embodiments, the organomanganese source contains a six-membered conjugated chelate ring. This six-membered conjugated chelate ring structure, on the one hand, utilizes its conjugation and chelation effects to form stable coordination with manganese ions, allowing for the slow and uniform release of manganese during sintering. This facilitates full interaction with thiol-containing organic compounds and the directional formation of Mn-S bond repair sites, avoiding the formation of local impurity phases due to the instantaneous and violent decomposition of the manganese source. On the other hand, this conjugated structure can effectively regulate the electron cloud density of the central manganese ion, endowing it with a suitable Mnn concentration. 2+ / Mn 3+The redox potential constitutes a mild, single-center reversible variable valence system, which can effectively provide / accept electrons to absorb overcharge during electrochemical processes, without causing violent decomposition of the electrolyte or cracking of the material surface structure due to excessive oxidizing properties. This significantly improves the structural stability and overcharge tolerance of the material. As a possible implementation method, the organic manganese source includes one or more of manganese acetylacetone, manganese benzoylacetone, manganese hexafluoroacetylacetone, and manganese dibenzoylmethane.

[0085] It should be noted that the oxidation state of manganese in organic manganese sources is +3. The chemical formula for manganese acetylacetone is Mn(acac)3, where acac = CH3COCHCOCH3. - The chemical formula of manganese benzoylacetone is Mn(bzac)3, where bzac = C6H5COCHCOCH3. - The chemical formula of manganese hexafluoroacetylacetone is Mn(hfac)3.

[0086] Hfac=CF3COCHCOCF3 - The chemical formula of manganese dibenzoylmethane is Mn(dbm)3, where dbm = C6H5COCHCOC6H5 - .

[0087] In some embodiments, the thiol-containing organic compounds include one or more of the following: thiol-containing amino acids, thiol-containing carboxylic acids, and thiol-containing alcohols.

[0088] As one possible implementation, the thiol-containing amino acid includes one or more of L-cysteine, D-cysteine, L-homocysteine, and L-cysteine.

[0089] In some embodiments, the mass percentage of manganese in the organomanganese source relative to the mass of the first system is 0.21%-0.72%; for example, it can be, but is not limited to, 0.21%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, 0.4%, 0.42%, 0.44%, 0.46%, 0.48%, 0.5%, 0.52%, 0.54%, 0.56%, 0.58%, 0.6%, 0.62%, 0.64%, 0.66%, 0.68%, 0.7%, 0.72%, or any range between any two of the above values. Thus, manganese ions can suppress oxygen vacancy migration through lattice pinning effect, while simultaneously delaying carrier recombination.

[0090] In some alternative embodiments, the manganese element contained in the organic manganese source is 0.26%-0.64% of the mass of the first system.

[0091] As one possible implementation, the thiol-containing organic compound accounts for 0.5%-1.5% of the mass of the first system; for example, it can be, but is not limited to, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, or any range between two of the above values. Thus, this concentration range, by precisely controlling the reactivity and side reaction threshold, can maximize the functionality of the thiol group while maintaining system stability.

[0092] In some alternative implementations, the thiol-containing organic compound accounts for 0.8%-1.2% of the mass of the first system.

[0093] In some embodiments, the temperature of the first sintering treatment is 650°C-790°C; for example, it can be, but is not limited to, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, or any range between two of the above temperatures. During the heating of the first system to the sintering temperature, in the low-temperature range of 350℃-380℃, manganese elements in the organic manganese source form Mn-S coordination bonds with thiol groups in the thiol-containing organic matter. Simultaneously, through surface lattice oxygen bridging with iron ions in lithium iron phosphate, a Mn-O-Fe bridging structure is formed, occupying iron sites and blocking the formation pathway of Fe-S bonds. After heating to the sintering temperature, during the high-temperature sintering process, with the Mn-S coordination structure as the core, the carbon chains in the thiol-containing organic matter undergo pyrolysis and structural rearrangement, generating a gradient interface layer with Mn-SNC distribution in situ. The N-rich component optimizes the interfacial lithium-ion transport. The above processes simultaneously achieve iron dissolution suppression, lithium-ion diffusion channel optimization, and a significant improvement in overcharge performance.

[0094] As one possible implementation, the first sintering treatment time is 5h-12h; for example, it can be, but is not limited to, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any range between the above two times.

[0095] In some embodiments, the first carbon source accounts for 0.5%-5% of the mass of the first system; for example, it can be, but is not limited to, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any range between two of the above mass percentages. This helps to ensure the reducing atmosphere of the first sintering process and provides a basic carbon coating layer.

[0096] As one possible implementation, the first carbon source includes at least one of glucose, sucrose, fructose, starch, polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol.

[0097] In some embodiments, the method for preparing the lithium iron phosphate material to be treated includes: providing a second system comprising an iron source, a phosphorus source, a lithium source, and a second carbon source; drying the second system to prepare the material to be sintered; and performing a second sintering treatment on the material to be sintered under a second inert atmosphere to prepare the lithium iron phosphate material to be treated.

[0098] It should be noted that in this article, terms such as "first inert atmosphere," "second inert atmosphere," "first carbon source," "second carbon source," "first system," "second system," "first sintering treatment," and "second sintering treatment" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be interpreted as implicitly indicating the importance or quantity of the indicated technical features. Furthermore, terms such as "first" and "second" serve only as a non-exhaustive enumeration and should be understood as not constituting a closed limitation on quantity.

[0099] In some alternative embodiments, the first inert atmosphere and the second inert atmosphere each independently comprise one or more of nitrogen, argon, and helium.

[0100] As one possible implementation, the molar ratio of lithium in the lithium source to iron in the iron source is (1.02-1.1):1; for example, it can be, but is not limited to, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1, 1.1:1, or any range between any two of the above molar ratios.

[0101] In some embodiments, the molar ratio of iron in the iron source to phosphorus in the phosphorus source is (0.96-0.985):1; for example, it can be, but is not limited to, 0.96:1, 0.965:1, 0.97:1, 0.975:1, 0.98:1, 0.985:1, or any range between any two of the above molar ratios.

[0102] In some embodiments, the mass percentage of the second carbon source in the second system is 0.5%-5%; for example, it can be, but is not limited to, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any range between any two of the above mass percentages.

[0103] In some embodiments, the temperature of the second sintering treatment is 500°C-800°C; for example, it can be, but is not limited to, 500°C, 600°C, 700°C, 800°C or any range between two of the above temperatures.

[0104] As one possible implementation, the second sintering treatment time is 3h-10h; for example, it can be, but is not limited to, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or any range between the above two times.

[0105] In some embodiments, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium phosphate, lithium dihydrogen phosphate, and lithium acetate.

[0106] As one possible implementation, the iron source includes one or more of ferric oxide, iron tetroxide, ferric hydroxide, ferric nitrate, and ferric phosphate.

[0107] In some embodiments, the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium phosphate, and lithium dihydrogen phosphate.

[0108] In some embodiments, the second carbon source includes one or more of glucose, sucrose, fructose, starch, polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol.

[0109] As one possible implementation, the second system also includes additives.

[0110] In some alternative embodiments, the additive includes a compound containing an element M, which includes one or more of Ti, V, Nb, Mg, W, and Y.

[0111] In some optional embodiments, the additive accounts for 0.1%-2% of the mass of the second system; for example, it can be, but is not limited to, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, or any range between any two of the above mass percentages.

[0112] The third aspect of this application provides a secondary battery, including at least one of the lithium iron phosphate material of the first aspect of this application and the lithium iron phosphate material prepared by the preparation method of the second aspect of this application.

[0113] The technical solutions of this application will be described in detail below with reference to specific embodiments. It should be understood that these embodiments are only for illustrating this application and are not intended to limit the scope of this application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application, or follow experimental manuals or conventional conditions in the field, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the field.

[0114] In the specific embodiments described below, the measurement parameters involving raw material components may have slight deviations within the weighing accuracy range unless otherwise specified. Temperature and time parameters are subject to acceptable deviations due to instrument testing accuracy or operational precision.

[0115] Unless otherwise specified, all raw materials in the following examples and comparative examples are commercially available or prepared using conventional methods.

[0116] It should be noted that the oxidation state of manganese in the organic manganese source used in the following embodiments is +3.

[0117] I. Preparation of Lithium Iron Phosphate Materials

[0118] Example 1

[0119] Step 1: Weigh out iron phosphate, lithium carbonate, glucose, PEG2000, and titanium dioxide sequentially, and add them to deionized water to form a second system. In this second system, the iron-to-phosphorus ratio is 0.968, the molar ratio of Li to Fe is 1.03:1, the additive (titanium dioxide) accounts for 1.2% of the dry weight of the second system, and the second carbon source (glucose and PEG2000) accounts for 2.4% of the dry weight of the second system. Ball mill the second system for 50 minutes. Then, pass the slurry into a pin mill and mill for 70 minutes to obtain a slurry with a particle size Dv50 of 500 nm and a solid content of 40.79%.

[0120] Step 2: Spray dry the slurry obtained in Step 1, and sinter the obtained spray material in a nitrogen atmosphere furnace. The temperature of the first sintering treatment is 800℃, and the reaction is kept at a constant temperature for 10 hours. After the temperature drops to room temperature, the sintered material is crushed and sieved to obtain the first sintered material.

[0121] Step 3: Sequentially weigh the primary sintering material, glucose, PEG2000, manganese acetylacetone (Mn(C5H7O2)3), and L-cysteine, and mix them using a plow mixer to form the first system. The mass percentages of manganese acetylacetone and L-cysteine ​​in the first system are 2% and 1%, respectively, and the mass percentage of the first carbon source (glucose and PEG2000) is 2.58%. Mix the first system in a plow mixer for 20 minutes.

[0122] Step 4: The mixture obtained in Step 3 is subjected to secondary sintering in a nitrogen atmosphere furnace. The temperature of the secondary sintering is 750℃, and the reaction is carried out at a constant temperature for 10 hours. After the temperature drops to room temperature, the secondary sintered material is subjected to air jet milling. The frequency of the classifier wheel of the air jet mill is adjusted to 115Hz to obtain lithium iron phosphate material.

[0123] Example 2

[0124] The preparation method of Example 2 is similar to that of Example 1, except that: in step 3 of Example 2, the mass percentages of manganese acetylacetone and L-cysteine ​​in the first system are 2% and 1% respectively, and the mass percentage of the first carbon source (glucose and PEG2000) in the first system is 5%; all other aspects are the same.

[0125] Example 3

[0126] The preparation method of Example 3 is similar to that of Example 1, except that: in step 3 of Example 3, the mass percentages of manganese acetylacetone and L-cysteine ​​in the first system are 4% and 1% respectively, and the mass percentage of the second carbon source (glucose and PEG2000) in the first system is 0.5%; all other aspects are the same.

[0127] Example 4

[0128] The preparation method of Example 4 is similar to that of Example 1, except that: in step 3 of Example 4, the mass percentages of manganese acetylacetone and L-cysteine ​​in the first system are 1.38% and 0.5%, respectively; all other aspects are the same.

[0129] Example 5

[0130] The preparation method of Example 5 is similar to that of Example 1, except that: in step 3 of Example 5, the mass percentages of manganese acetylacetone and L-cysteine ​​in the first system are 1.7% and 0.8%, respectively; all other aspects are the same.

[0131] Example 6

[0132] The preparation method of Example 6 is similar to that of Example 1, except that: in step 3 of Example 6, the mass percentages of manganese acetylacetone and L-cysteine ​​in the first system are 4.1% and 1.2%, respectively; all other aspects are the same.

[0133] Example 7

[0134] The preparation method of Example 7 is similar to that of Example 1, except that: in step 3 of Example 7, the mass percentages of manganese acetylacetone and L-cysteine ​​in the first system are 4.6% and 1.5%, respectively; all other aspects are the same.

[0135] Example 8

[0136] The preparation method of Example 8 is similar to that of Example 1, except that vanadium pentoxide is used instead of titanium dioxide in step 1 of Example 8; all other aspects are the same.

[0137] Example 9

[0138] The preparation method of Example 9 is similar to that of Example 1, except that aluminum oxide is used instead of titanium dioxide in step 1 of Example 9; all other aspects are the same.

[0139] Example 10

[0140] The preparation method of Example 10 is similar to that of Example 1, except that the additive in step 1 of Example 10 accounts for 0.1% of the dry weight of the second system; all other aspects are the same.

[0141] Example 11

[0142] The preparation method of Example 11 is similar to that of Example 1, except that: in step 3 of Example 11, benzoyl acetone manganese is used instead of acetylacetone manganese, and the mass ratio of manganese in benzoyl acetone manganese in the first system is the same as the mass ratio of manganese in acetylacetone manganese in the first system in Example 1; all other aspects are the same.

[0143] Example 12

[0144] The preparation method of Example 12 is similar to that of Example 1, except that: in step 3 of Example 12, manganese hexafluoroacetylacetone is used instead of manganese acetylacetone, and the mass ratio of manganese in the first system is the same as that of manganese in the first system in Example 1; all other aspects are the same.

[0145] Example 13

[0146] The preparation method of Example 13 is similar to that of Example 1, except that: in step 3 of Example 13, manganese dibenzoylmethane is used instead of manganese acetylacetone, and the mass ratio of manganese in the first system is the same as that in the first system of manganese acetylacetone in Example 1; all other aspects are the same.

[0147] Example 14

[0148] The preparation method of Example 14 is similar to that of Example 1, except that D-cysteine ​​is used instead of L-cysteine ​​in step 3 of Example 14; all other aspects are the same.

[0149] Example 15

[0150] The preparation method of Example 15 is similar to that of Example 1, except that L-homocysteine ​​is used instead of L-cysteine ​​in step 3 of Example 15; all other steps are the same.

[0151] Example 16

[0152] The preparation method of Example 16 is similar to that of Example 1, except that L-cysteine ​​is used instead of L-cysteine ​​in step 3 of Example 16; all other aspects are the same.

[0153] Comparative Example 1

[0154] The preparation method of Comparative Example 1 is similar to that of Example 1, except that: in step 3 of Comparative Example 1, aluminum oxide is used to replace manganese acetylacetone and L-cysteine, and the mass percentage of aluminum oxide in the first system is 3%; all other aspects are the same.

[0155] Comparative Example 2

[0156] The preparation method of Comparative Example 2 is similar to that of Example 1, except that: in step 3 of Comparative Example 2, vanadium pentoxide is used to replace manganese acetylacetone and L-cysteine, and the mass percentage of vanadium pentoxide in the first system is 3%; all other aspects are the same.

[0157] Comparative Example 3

[0158] The preparation method of Comparative Example 3 is similar to that of Example 1, except that: in step 3 of Comparative Example 3, cobalt oxide is used instead of manganese acetylacetone and L-cysteine, and the mass percentage of cobalt oxide in the first system is 3%; all other aspects are the same.

[0159] Comparative Example 4

[0160] The preparation method of Comparative Example 4 is similar to that of Example 1, except that only manganese acetylacetone is added in step 3 of Comparative Example 4, and L-cysteine ​​is not added. The mass percentage of manganese acetylacetone in the first system is 3%; all other aspects are the same.

[0161] Comparative Example 5

[0162] The preparation method of Comparative Example 5 is similar to that of Example 1, except that only L-cysteine ​​is added in step 3 of Comparative Example 5, and no manganese acetylacetone is added. The mass percentage of L-cysteine ​​in the first system is 3%; all other aspects are the same.

[0163] The differences between the above embodiments and comparative examples are shown in Table 1.

[0164] Table 1

[0165]

[0166] In Table 1, mass percentage 1 refers to the mass percentage of manganese in the first system, or the mass percentage of the comparative dopant in Comparative Examples 1-3 in the first system; mass percentage 2 refers to the mass percentage of thiol-containing organic matter in the first system; and the amount of the first carbon source refers to the mass percentage of the first carbon source in the first system in step 3.

[0167] II. Performance Testing

[0168] The lithium iron phosphate materials prepared in the above embodiments and comparative examples were subjected to the following tests:

[0169] 1. Dv50: Tested using a Malvern 3000 laser particle size analyzer.

[0170] 2. Carbon Content: The lithium iron phosphate material to be tested is heated and burned in an oxygen stream in a high-frequency induction furnace. The generated carbon dioxide and sulfur dioxide are carried by the oxygen to the measuring chamber of an infrared analyzer. Since carbon dioxide and sulfur dioxide absorb infrared energy of specific wavelengths, their absorption energy is proportional to their concentration. The carbon and sulfur content of the sample can be measured based on the change in energy received by the detector. For specific operating procedures, refer to standard GB / T 20123-2006.

[0171] 3. Compacted Density: Place the lithium iron phosphate material to be tested on a compaction mold of known diameter (the mold is a Sansi Zongheng UTM7305). The mold has a metal sheet at the top and bottom, with the powder placed in the middle. Apply a pressure of 3T while simultaneously measuring the corresponding powder thickness. Calculate the compacted density using the formula ρ=m / v. Specific procedures should refer to standard GB / T24533-2009.

[0172] 4. Specific surface area: The lithium iron phosphate material to be tested is placed in a U-shaped sample tube, and a mixed gas containing adsorbate molecules (N2) is passed through the sample. The amount of adsorbate molecules (N2) adsorbed by the sample is determined based on the change in gas concentration before and after adsorption. Specific operation should refer to the standard: GB / T 13390-2008.

[0173] 5. Iron leaching: Immerse 5g of the lithium iron phosphate material to be tested in 50ml of deionized water for 6 hours, then filter it through a 0.45μm inert filter membrane, and perform a volume adjustment test using ICP-OES. For specific test methods, refer to the standard: GC / T 30835-2014.

[0174] 6. Charge / discharge specific capacity and overcharge safety performance:

[0175] The lithium iron phosphate cathode materials prepared in the above embodiments and comparative examples were mixed with conductive agent Super P and binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent. The mixture was thoroughly ground and stirred to form a uniform slurry. The slurry was uniformly coated on one side of an aluminum foil current collector and vacuum dried at 120°C for 12 hours. After rolling and cutting, the cathode sheet was obtained, with the active material loading controlled at 1.5-2.0 mg / cm³. 2 .

[0176] A lithium metal sheet was used as the negative electrode. A Celgard 2400 polypropylene membrane was used as the separator. The electrolyte solvent consisted of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a 1:1 volume ratio, with a LiPF6 concentration of 1 mol / L. CR2032 coin cells were assembled in an argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm).

[0177] Charge / discharge specific capacity: at 25℃,

[0178] Charge the battery at a constant current rate of 1C to 3.5V, then charge it at a constant voltage rate of 3.5V until the current is equal to 0.05C. The charging capacity at this time is recorded as the 1C charging specific capacity. After that, let it stand for 5 minutes, and then discharge it at a constant current rate of 1C until the voltage is 2.0V. The discharge capacity at this time is recorded as the 1C discharge specific capacity.

[0179] Overcharge safety performance: Charge the battery at a rate of 0.5C from 3.5V to 5.5V at room temperature. Calculate the charging time required. The shorter the total time to charge to 5.5V, the better the overcharge performance.

[0180] The test results for each of the above implementations and comparative examples are shown in Table 2.

[0181] Table 2

[0182]

[0183] As shown in Table 2, using organic manganese sources and thiol-containing organic compounds as dopants during the preparation of lithium iron phosphate materials can effectively reduce the amount of iron leaching under high compaction density and improve the overcharge performance of the materials. The reason for this is that during the sintering process, the manganese element in the organic manganese source forms Mn-S coordination bonds with the thiol groups in the thiol-containing organic compounds. These molecular pairs, formed by the organic manganese source and the thiol-containing organic compounds, construct Mn-S bond repair sites on the surface of the lithium iron phosphate material to be treated, directionally passivating iron vacancies and inhibiting electrolyte erosion, thus preventing iron ion dissolution and improving the overcharge performance of the material.

[0184] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0185] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A lithium iron phosphate material, characterized in that, It includes lithium iron phosphate particles and a carbon coating layer covering at least a portion of the surface of the lithium iron phosphate particles. The lithium iron phosphate particles are doped with manganese and sulfur elements, and at least a portion of the manganese and at least a portion of the sulfur elements form Mn-S coordination bonds.

2. The lithium iron phosphate material as described in claim 1, characterized in that, From the center of the lithium iron phosphate particle radially to its outer surface, the concentration distribution of both manganese and sulfur elements shows an increasing trend.

3. The lithium iron phosphate material as described in claim 1, characterized in that, In the Mn-S coordination bond, the manganese element is connected to its neighboring iron element through a lattice oxygen bridge; and / or, The lithium iron phosphate material is also doped with nitrogen.

4. The lithium iron phosphate material according to any one of claims 1 to 3, characterized in that, The mass percentage of manganese in the lithium iron phosphate material is 0.26%-0.64%; and / or, The Dv50 of the lithium iron phosphate material is 1100nm-1500nm, optionally 1200nm-1400nm; and / or, The specific surface area of ​​the lithium iron phosphate material is 9m². 2 / g-14m 2 / g, optional 10m 2 / g-12m 2 / g; and / or, The carbon coating layer comprises 1.05%-1.35% by mass in the lithium iron phosphate material; and / or, The lithium iron phosphate particles also contain element M, which includes one or more of Ti, V, Nb, Mg, W, and Y; and / or, The compaction density of the lithium iron phosphate material is 2.55 g / cm³. 3 -2.6g / cm 3 .

5. A method for preparing lithium iron phosphate material, characterized in that, Includes the following steps: The lithium iron phosphate material is prepared by first sintering a first system comprising the lithium iron phosphate material to be treated, an organomanganese source, a mercapto-containing organic compound, and a first carbon source under a first inert atmosphere.

6. The method for preparing lithium iron phosphate material as described in claim 5, characterized in that, The organic manganese source contains a six-membered conjugated chelate ring; Optionally, the organic manganese source includes one or more of manganese acetylacetone, manganese benzoylacetone, manganese hexafluoroacetylacetone, and manganese dibenzoylmethane; and / or, The thiol-containing organic compounds include one or more of thiol-containing amino acids, thiol-containing carboxylic acids, and thiol-containing alcohols; Optionally, the thiol-containing amino acid includes one or more of L-cysteine, D-cysteine, L-homocysteine, and L-cysteine.

7. The method for preparing lithium iron phosphate material as described in claim 5, characterized in that, The percentage of manganese in the organic manganese source relative to the mass of the first system is 0.21%-0.72%, optionally 0.26%-0.64%; and / or, The mass percentage of the thiol-containing organic compound in the first system is 0.5%-1.5%, and can be selected as 0.8%-1.2%.

8. The method for preparing lithium iron phosphate material as described in claim 5, characterized in that, The first sintering treatment is carried out at a temperature of 650℃-790℃ for 5-12 hours; and / or, The first carbon source accounts for 0.5%-5% of the mass of the first system; and / or, The first carbon source includes at least one of glucose, sucrose, fructose, starch, polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol.

9. The method for preparing lithium iron phosphate material according to any one of claims 5 to 8, characterized in that, The preparation method of the lithium iron phosphate material to be treated includes: A second system is provided, including iron source, phosphorus source, lithium source and second carbon source; The second system is dried to prepare the material to be sintered; Under a second inert atmosphere, the material to be sintered is subjected to a second sintering treatment to prepare the lithium iron phosphate material to be treated. Optionally, the molar ratio of lithium in the lithium source to iron in the iron source is (1.02-1.1):1; Optionally, the molar ratio of iron in the iron source to phosphorus in the phosphorus source is (0.96-0.985):1; Optionally, the second carbon source accounts for 0.5%-5% of the mass of the second system; Optionally, the temperature of the second sintering treatment is 500℃-800℃, and the time is 3h-10h; Optionally, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium phosphate, lithium dihydrogen phosphate, and lithium acetate; Optionally, the iron source includes one or more of ferric oxide, iron(II) oxide, ferric hydroxide, ferric nitrate, and ferric phosphate; Optionally, the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium phosphate, and lithium dihydrogen phosphate; Optionally, the second carbon source includes one or more of glucose, sucrose, fructose, starch, polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol; Optionally, the second system further includes additives; Further optionally, the additive includes a compound containing element M, wherein element M includes one or more of Ti, V, Nb, Mg, W and Y; Further optionally, the additive accounts for 0.1%-2% of the mass of the second system.

10. A secondary battery, characterized in that, It includes at least one of the lithium iron phosphate materials according to any one of claims 1 to 4 and the lithium iron phosphate materials prepared by the preparation method according to any one of claims 5 to 9.